2003
DOI: 10.1029/2001jd001412
|View full text |Cite
|
Sign up to set email alerts
|

Regional background ozone and carbon monoxide variations in remote Siberia/East Asia

Abstract: [1] Continuous measurements of O 3 and CO were made during 1997-1999 at Mondy, a remote mountain site in East Siberia, in order to quantify their mixing ratios and their climatology in the ''background'' troposphere of continental Eurasia. The seasonal cycles of O 3 and CO show the spring maximum-summer minimum similar to that previously reported in the remote Northern Hemisphere. The influences of Siberian forest fires on the variations of CO mixing ratios at Mondy were observed both on a local and a regional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
91
2
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(101 citation statements)
references
References 70 publications
5
91
2
2
Order By: Relevance
“…However, the main focus is mostly at data from Cape Hedo as the station is most relevant to the ideal outflow condition due to the minimized effects of emissions from Japan mainland and Korea. Previous studies at most of these sites confirmed the regional representative of the sites and more details have been previously explained and could be found elsewhere (Pochanart et al, 2004(Pochanart et al, , 2003(Pochanart et al, , 2002(Pochanart et al, , 1999. In Fig.…”
Section: Observation and Methodologysupporting
confidence: 71%
See 2 more Smart Citations
“…However, the main focus is mostly at data from Cape Hedo as the station is most relevant to the ideal outflow condition due to the minimized effects of emissions from Japan mainland and Korea. Previous studies at most of these sites confirmed the regional representative of the sites and more details have been previously explained and could be found elsewhere (Pochanart et al, 2004(Pochanart et al, , 2003(Pochanart et al, , 2002(Pochanart et al, , 1999. In Fig.…”
Section: Observation and Methodologysupporting
confidence: 71%
“…The instrumental systems and monitoring criteria for ozone in this study are similar to those of our previous studies and details regarding ozone measurement, calibration, regular maintenance and data handling have been reported elsewhere (Tanimoto et al, 2007;Pochanart et al, 2003Pochanart et al, , 1999. The isentropic backward trajectories were applied in order to look for the evidence of direct episodic transboundary ozone transport events from a region nearby Chinese sites in central eastern China to Japanese site.…”
Section: Observation and Methodologymentioning
confidence: 96%
See 1 more Smart Citation
“…In the interior region of the Asian continent, a summer maximum of O 3 was observed over the northeastern Tibet-Qinghai Plateau (Wang et al, 2006b), which has been attributed to a possible source of stratosphere-to-troposphere exchange . For the broad mid-tropospheric summer maximum of O 3 over Beijing, another important source may be the biomass burnings in Central Asia and Russia (Pochanart et al, 2003;Nedelec et al, 2005;Qin et al, 2006), whose plumes can be rapidly transported to middle and even upper troposphere by warm conveyor belts Real et al, 2007).…”
Section: Diurnal Variation Of Lower Tropospheric Omentioning
confidence: 99%
“…For these years, the variation in CO does not follow the variation in the number of fires. The large region selected over Siberia is known to also be impacted by CO-enriched plumes transported from other regions, such as polluted air masses from China (e.g., Paris et al, 2008) or from Europe (e.g., Pochanart et al, 2003). These external influences interfere with the CO plumes originating from forest fires measured over this region.…”
Section: The Iasi Data Usedmentioning
confidence: 99%